Optimization of aqueous extraction of blue dye from butterfly pea flower - Ashwini, Baskaran; Siti Kholijah Abdul, Mudalib; Izhab, Izirwan (IOP Publishing, 2019)
Dyes are widely used in industries such as textiles, leather, paper, and plastics to colourthefinal products. People use natural sources such as stem, bark, leaves, roots and flowers to get different coloursfor dyeing purposes. In addition, natural colorants such as anthocyanins are known for their possible health benefits as dietary antioxidants. The objectivesof this study areto extract the blue dyefrom the butterfly pea flower using maceration method and to determine the optimum condition by response surface methodology. The flowers weredried, grinded and went through the maceration method for the extraction process. Response surface models were developed correlating the extraction yield with three parameters namely residence time, temperature and solid to liquid ratio. The result from this experiment was optimized using response surface methodology to obtain the optimum condition at temperature 54 °C, extraction time 74minutes and solid-to-liquid ratio of 1:37to give extraction yield of 45.51%.